The Wikipedia revolution how a bunch of nobodies created the world's greatest encyclopedia - Lih, Andrew (Tantor Media, 2009)
Details Wikipedia's site's inception in 2001, its evolution, and its remarkable growth, while explaining its larger cultural repercussions.
Unabridged. - Audio file. - Title from image on Web page (viewed May 18, 2009). - Previously released on compact disc, 2009
Keywords: Wikipedia; Electronic encyclopedias; User-generated content; Encyclopédies électroniques; Contenu créé par l'utilisateur; Downloadable audio books; Audiobooks; Livres audio